Penguatan Moderasi Beragama pada Anak Usia Dini sebagai Upaya Pencegahan Radikalisme di Masa Pandemi Covid- 19 - Amala., Nisa`el; Reswari, Ardhana; Iftitah, Selfi Lailiyatul (Proceedings of Annual Conference for Muslim Scholars, 2022)
Polemics of radicalism continue to emerge in early childhood education and radical movements have explored and involved in early childhood. Strengthening moderate Islam in early childhood must be carried out from an early age through educational arrangements that are programmed and adapted to the stages of child development characteristics so that children have moderate values and prevent children from having radical ideas later in life. The purpose of this study was to determine the strength of religious moderation in early childhood as an effort to prevent radicalism during the Covid-19 pandemic. The golden period of early childhood is the most appropriate time to implement the values of religious moderation so that later a strong Islamic foundation is formed in children so that they can ward off radicalism in the future. During this pandemic, learning activities, especially to strengthen understanding of religious moderation in schools, are carried out online or blended learning which is a combination of face-to-face and the use of information technology in implementation. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses the Mile and Huberman model, namely data reduction, display, and verification. The results of this study indicate that strengthening religious moderation in early childhood is an effort to prevent radicalism during the Covid-19 pandemic. The strengthening of religious moderation consists of four components, namely instilling national commitment, tolerance, introducing and preserving local culture, and anti-violence. The strengthening of religious moderation is given so that children have moderate values and are a form of prevention against radicalism in the future.